Tata Kelola Berkontribusi dan Kualitas Layanan Elektronik Perusahaan Pelayaran Nasional - Taufik Akbar; Asep Suparman; Sandriana Marina; Edhie Budi Setiawan; Rully Indrawan (Institut Transportasi dan Logistik Trisakti, 2022)
The purpose of the study is to determine the contribution of SIMLALA service governance and the quality of electronic services to the satisfaction of shipping companies. Some of the main problems were the limited number of SIMLALA service operators, the lack of satisfaction of shipping companies with the quality of SIMLALA electronic services of the Directorate of Sea Traffic and Transportation, and the inadequate governance of marine traffic services of the Directorate. This study used path analysis with 133 samples of shipping companies taken randomly. The findings of this study are the Directorate of Sea Traffic and Transportation issues an accelerative policy to support the improvement of the quality of SIMLALA electronic services. The Directorate also issues specific policies to manage the governance of sea traffic services. The Directorate should try to improve and enhance the quality of SIMLALA electronic services to make a greater contribution for the shipping companies.